Integrated Project Management System to Improve Project Manajement Practice. Case: Inhouse Brownfield Project PT. Freeport Indonesia Concentrating Division - Widyatmoko, Adi Nugroho; Firman, Aries F (The Indonesian Journal of Business Administration, 2017)
Abstract - PT Freeport Indonesia (PTFI) is a contractor of the Government of Indonesia (GOI) and a Freeport-McMoran Copper & Gold Inc. (FCX) subsidiary which is operating in Papua, the most eastern province in Indonesia. PTFI concentrator plant which have been operated since 1973 can be categorized as an old plant. As an old plant, PTFI concentrator plant required a lot of brownfield project due to following issues: a lot of production equipment require to be replaced due to their parts no longer supplied by the manufacturer, corrosion severity which are caused by interaction between steel and copper concentrate, and unpredictable ore hardness level.  Therefore, a lot of re-engineered and brownfield project required in order to keep the plant operated as the design capacity. However, due to lack of project management system, PTFI also experienced frequent project delay and cost overrun due to various problem. As a company, PTFI also doesn’t have criteria in term of what are the successful project criteria which are applicable within PTFI brownfield project. Therefore PTFI require to develop successful project criteria according to PTFI condition, identify and mapping the problems which are causing frequent project delay and cost overrun. By developing the successful project criteria, the integrated project management system can be developed in order to achieve those criteria. Moreover, the integrated project management system also expected can solve the problems which are frequently causing project delay and cost overrun. Successful project criteria and root cause analysis are developed using mind mapping by interviewing various respondents from various sections which are frequently involved within PTFI Concentrating Division brownfield project. According to the qualitative research analysis, the successful project criteria which are suitable with PTFI condition are as follows: according to specification, on time, safety, on budget, free from defects and doing the right thing. While the root cause which are causing frequent project delay and cost overrun are as follows: lack of project management business process, lack of project management documentation system, lack of project approval system, lack of define scope and collect project requirements and lack of procurement management. In order to solve the root cause, this research propose to improving the existing project management process according to project management process which are described in PMBOK 5th edition including develop project charter during project initiation phase, stakeholder identification process, plan scope management, develop an installation drawing and field check during project planning phase and develop lesson learned for future reference within improved business process. the other recommendation within this research also develop an Engineering Change Notice system, implementation of Project Management Offices (PMOs) as project approval and project prioritization committee, and develop a material control team. However, due to limitation of manpower, each of proposed solutions required to be selected and prioritized. In order to prioritize them, Pareto analysis is used. Therefore according to Pareto analysis, in order to solve 80% of frequent project the solutions require to be implemented are Implementation of Project Management Office (PMO) as project approval, selection and prioritization committee and improving existing project management business process according to the PMBOK.Keywords: Brownfield Project, Project Management, Successful Project Criteria, Mind Mapping, Project Management Process, Engineering Change Notice, Project Management Offices (PMOs), Pareto Analysis